2012
DOI: 10.1098/rstb.2012.0016
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic variability in dryland regions: impacts on ecosystem dynamics and food security

Abstract: Research on ecosystem and societal response to global environmental change typically considers the effects of shifts in mean climate conditions. There is, however, some evidence of ongoing changes also in the variance of hydrologic and climate fluctuations. A relatively high interannual variability is a distinctive feature of the hydrologic regime of dryland regions, particularly at the desert margins. Hydrologic variability has an important impact on ecosystem dynamics, food security and societal reliance on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 133 publications
3
64
0
Order By: Relevance
“…Moreover, SWA shows a stronger difference between dry and wet periods, has clearer unimodal shapes along the MAP gradient and possesses higher variability along the MAP gradient. This agrees with the hypothesized higher β dynamics in regions with higher interannual variability of annual rainfall [36,37], such as SWA (Figure 3a). In addition, this suggests that a higher rain use efficiency, which has been observed during dry periods [18], might be particularly favoured by greater rainfall variability.…”
Section: Vegetation Response To Rainfall Along Map Gradientssupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, SWA shows a stronger difference between dry and wet periods, has clearer unimodal shapes along the MAP gradient and possesses higher variability along the MAP gradient. This agrees with the hypothesized higher β dynamics in regions with higher interannual variability of annual rainfall [36,37], such as SWA (Figure 3a). In addition, this suggests that a higher rain use efficiency, which has been observed during dry periods [18], might be particularly favoured by greater rainfall variability.…”
Section: Vegetation Response To Rainfall Along Map Gradientssupporting
confidence: 89%
“…However, no attempt to describe any ecosystem-specific reaction to above or below average rainfall conditions with respect to ecohydrological traits such as β has been made on a regional scale based on gridded data. Additionally, there is evidence that greater environmental heterogeneity (such as rainfall variability) affects the way ecosystems react with changing resource availability [35,36]. Lázaro-Nogal et al [37] found greater phenotypic plasticity…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, SWA shows a stronger difference between hydroclimatic periods (dry vs. wet), has clearer unimodal shapes along the MAP gradient and possesses higher spatial variability. This agrees with the hypothesized 35 higher β plasticity in regions with pronouncedly higher interannual variability in rainfall amounts (D'Odorico and Bhattachan, 2012;Lázaro-Nogal et al, 2015), such as SWA (Fig. 2b).…”
Section: Vegetation Response To Rainfall Along Map Gradientssupporting
confidence: 85%
“…Additionally, there is evidence that greater environmental heterogeneity (such as rainfall variability) affects the way ecosystems react on changing resource availability (D'Odorico and Bhattachan, 2012;Holmgren et al, 2013). Lázaro-Nogal et al (2015) found greater phenotypic plasticity being associated with higher rainfall variability in dryland plant communities which is considered an important feature for dryland ecosystems in face of future changes in rainfall.…”
mentioning
confidence: 99%
“…It was argued that hydrological resilience was related more to vulnerability/sustainability than the reliability of water resources such as reservoir systems (e.g., [17]). Real hydrological systems (e.g., catchments) are complex [10,37,69] and have multiple attractors (steady states), which may inform how these systems may respond to and recover from perturbations such as droughts, floods, or groundwater pumping but determining multiple attractors is very challenging [20,21,33]. Selected factors (variables of concern) are often used indirectly to define or measure the resilience of hydrological systems.…”
Section: Entropy and Resilience Of Water Resourcesmentioning
confidence: 99%